2022
DOI: 10.1097/qco.0000000000000864
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Gram-negative bacteria during coronavirus disease 2019. What is the real pandemic?

Abstract: Purpose of reviewBacterial infections play a key role in hospital outcomes during the coronavirus disease 2019 (COVID-19) pandemic. Nonetheless, the global impact on the epidemiology of Gram-negative bacteria (GNB) and antibiotic resistance has not been clearly established.Recent findingsMultiple limitations exist in the current literature, in that substantial variability was observed with regard to methodology. Notwithstanding the heterogeneity, the evidence suggests that the COVID-19 pandemic had a substanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Langford et al reported that more than 60% of patients with COVID-19 who had a bacterial infection harbored a highly resistant organism [ 54 ]. However, multiple limitations intrinsic to the interpretation of COVID-19 data prevent accurate quantification of its impact on the global epidemiology of AMR [ 55 , 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…Langford et al reported that more than 60% of patients with COVID-19 who had a bacterial infection harbored a highly resistant organism [ 54 ]. However, multiple limitations intrinsic to the interpretation of COVID-19 data prevent accurate quantification of its impact on the global epidemiology of AMR [ 55 , 56 ].…”
Section: Methodsmentioning
confidence: 99%
“…Langford et al reported that over 60% of COVID-19 patients with bacterial infections had highly resistant microorganisms [54]. However, accurately quantifying the impact of COVID-19 on the global epidemiology of AMR is challenging due to limitations in interpreting COVID-19 data [55,56].…”
Section: український журнал клінічної хірургіїmentioning
confidence: 99%
“…Carbapenem-based empiric antibiotic regimens have long been associated with improved outcomes and, thus, comprised the backbone of antibiotic therapy for this patient population [ 8 ]. However, alarming is the emergence of carbapenem-resistant Gram-negative bacteria (CR-GNB), which has raised global concern due to limited remaining treatment options and overall poor prognosis with existing regimens [ 9 ]. As such, new terminology has been used to describe these pathogens, specifically Gram-negative pathogens with difficult-to-treat resistance (DTR), practically defined as treatment-limiting resistance to all first-line agents, that is, all β-lactams, including carbapenems and β-lactamase inhibitor combinations, and fluoroquinolones [ 10 ].…”
Section: Introductionmentioning
confidence: 99%